Expressions of secondary orality in written texts (not only) on the internet - Janečka, Martin (Bohemica Olomucensia, 2014)
I tried to sum up concisely and perhaps sufficiently for the purposes of this text, how the human society was developing in the ability of recording, categorizing, saving and transmitting information in different ages, what influence can history of these processes have on formation and state of the present-day culture. In other words - how the attributes of the primary (oral) culture were transmitted through the chirographic and typographic culture to the contemporary (visual) culture, which is legitimately called the secondary orality. I tried to transpose the theoretic-historical considerations into discussions about the relation between spoken and written forms of language that do not cooperate for various reasons. I came out of Vachek's distinction of written and spoken norm, where the function of the spoken norm is to react dynamically and the written norm reacts statically. I pointed out concrete examples from the language of internet, how these two norms collide.